Preserving a diffraction-limited beam in Ho:YAG laser using coherent polarization locking - Tan, L. H. (2013)
We overcome several thermal issues present in Ho:YAG lasers by distributing the gain over a larger volume and achieve a diffraction-limited beam using coherent polarization locking. Increased single-pass absorption, suppression of output power saturation, and improvement in beam quality were shown using the coherent polarization locking technique as compared to a conventional Ho:YAG laser cavity with the same pump and cavity configuration. Ten watts of CW Ho:YAG laser power was generated with >96% coherent combining efficiency.